Yield performance of Boro rice in response to urea super granular (USG) (Journal of the Bangladesh Agricultural University, 2016)
The experiment was conducted during December 2012 to June 2013 in the farmers field adjacent to Bangladesh Agricultural University (BAU), a village named Boira under Sadar Upazilla of Mymensingh to study the yield performance of Boro rice in response to USG. The experiment comprised two rice varieties viz. Binadhan-5 and BRRI dhan29 and seven levels of USG viz.i) prilled urea (PU) 280 kg ha-1(control),ii)USG 1.8g/4 hills in every alternate row applied at 5 cm depth, iii) USG 1.8g/4 hills in every alternate row applied at 10 cm depth, iv) USG 2.7g/4 hills in every alternate row applied at 5 cm depth, v)USG 2.7g/4 hills in every alternate row applied at 10 cm depth, vi) USG 3.6g/4 hills in every alternate row applied at 5 cm depth and vii)USG 3.6g/4 hills in every alternate row applied at 10 cm depth. The experiment was laid out in a randomized complete block design with three replications. Variety, level of USG and their interaction exerted significant influence on yield contributing characters and yield of Boro rice. BRRI dhan29 produced higher number of effective tillers hill-1 and heaviest grain than that of Binadhan-5. As a result of superior yield parameters, BRRI dhan29 gave higher yield (7.67 t ha-1) than Binadhan-5 (6.52 t ha-1). In case of USG, the highest number of total tillers hill-1, grains panicle-1, 1000-grain weight and grain yield (7.59 t ha-1) were obtained from USG @ 3.6g/4 hills in every alternate row applied at 5cm depth. The lowest values of all the parameters were obtained from PU. Considering their interaction effect, BRRI dhan29 with USG 3.6g/4 hills in every alternate row applied at 5cm depth produced best yield attributes, grain (8.38 t ha-1) and straw yield (9.26 t ha-1). The lowest performance was observed in Binadhan-5 with PU. The overall results suggest that farmers can be advised to cultivate BRRI dhan29 fertilized with USG 3.6g/4 hills in every alternate row at 5 cm depth for getting highest yield in Boro season under the agro-climate condition of the study area.J. Bangladesh Agril. Univ. 13(1): 13-17, June 2015